Pengembangan Sumber Daya Insani Dalam Meningkatkan Kinerja Karyawan UD Pribumi Jaya - R. Fakhrurrazi; Nihayatut Tasliyah; Rohiqi Mahtum (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2026)
This study aims to analyze human resource development strategies in improving employee performance at UD Pribumi Jaya. Human resource development is considered a crucial aspect in supporting company productivity and success, particularly in facing increasingly competitive business environments. This research employs a qualitative approach using a case study method. Data were collected through observation, interviews, and documentation. Primary data were obtained directly from the company’s management and employees, while secondary data were derived from relevant supporting documents. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings reveal that UD Pribumi Jaya implements several human resource development strategies, such as recruitment processes, work guidance, on-the-job training, motivation through reward systems, and regular performance evaluations. Job training appears to be the most dominant strategy, as it effectively enhances employees’ practical skills and accelerates work adaptation. Furthermore, motivation and periodic evaluation play significant roles in maintaining employee morale and continuously improving performance quality. However, several challenges were identified, including internal barriers such as training fatigue and limited workforce, as well as external barriers related to educational background mismatches with assigned tasks. Therefore, human resource development must be conducted consistently and systematically to improve employee performance and support the company’s sustainability.